ON NEW GRUSS TYPE INEQUALITIES FOR CONFORMABLE FRACTIONAL INTEGRALS - Mumcu, I; Set, E (TWMS journal of applied and engineering mathematics, 2019)
We use conformable fractional integral, recently introduced by Khalil et. al. and Abdeljavad, to obtain some new integral inequalities of Gruss type. We show two new theorems associated with Gruss inequality, as well as state and show new identities related to this fractional integral operator. Keywords: Gruss inequality, Riemann-Liouville fractional integrals, conformable fractional integrals. AMS Subject Classification: 26A33, 26D10, 33B20.